Bivalirudin versus heparin in patients undergoing percutaneous peripheral interventions: A systematic review and meta-analysis. (February 2019) - Olmedo, Wilman; Villablanca, Pedro A; Sanina, Cristina; Walker, Jonathan; Weinreich, Michael; Brevik, Jeannine; Avendano, Ricardo; Bravo, Claudio A; Romero, Jorge; Ramakrishna, Harish; Babaev, Anvar; Attubato, Michael; et al.
Background: Bivalirudin may be an effective alternative anticoagulant to heparin for use in percutaneous peripheral interventions. We aimed to compare the safety and efficacy of bivalirudin versus heparin as the procedural anticoagulant agent in patients undergoing percutaneous peripheral intervention. Methods: For this meta-analysis and systematic review, we conducted a search in PubMed, Medline, Embase, and Cochrane for all the clinical studies in which bivalirudin was compared to heparin as the procedural anticoagulant in percutaneous peripheral interventions. Outcomes studied included all-cause mortality, all-bleeding, major and minor bleeding, and access site complications. Results: Eleven studies were included in the analysis, totaling 20, 137 patients. There was a significant difference favoring bivalirudin over heparin for all-cause mortality (risk ratio 0.58, 95% CI 0.39–0.87), all-bleeding (risk ratio 0.62, 95% CI 0.50–0.78), major bleeding (risk ratio 0.61, 95% CI 0.39–0.96), minor bleeding (risk ratio 0.66, 95% CI 0.47–0.92), and access site complications (risk ratio 0.66, 95% CI 0.51–0.84). There was no significant difference in peri-procedural need for blood transfusions (risk ratio 0.79, 95% CI 0.57–1.08), myocardial infarction (risk ratio 0.87, 95% CI 0.59–1.28), stroke (risk ratio 0.77, 95% CI 0.59–1.01), intracranial bleeding (risk ratio 0.77, 95% CI 0.29–2.02), or amputations (OR 0.75, 95% CI 0.53–1.05). Conclusion: Our meta-analysis suggests that bivalirudin use for percutaneous peripheral interventions is associated with lower all-cause mortality, bleeding, and access site complications as compared to heparin. Further large randomized trials are needed to confirm the current results.